WHAT ARE THE BARRIERS TO THE IMPLEMENTATION OF ELECTRONIC MEDICAL RECORDS? A REVIEW OF RECENT STUDIES - Nurvita Wikansari; Dian Budi Santoso (Jurnal Riset Kesehatan, 2022)
Information technology utilization in the health sector is increasingly widespread. One aspect that cannot be separated from the intervention of information technology is medical records management through electronic medical records implementation. The number of healthcare facilities that implement electronic medical records is increasing. However, it is important to understand the various barriers that may be encountered in the electronic medical records implementation so that the success rate of implementation will be higher. This study aims to identify the current state of knowledge about electronic medical records implementation barriers. A literature review was conducted using three databases, PubMed, Science Direct, and Google Scholar using "electronic medical records'' and "implementation barriers" as keywords. There were 13 articles used in this study. There are 8 categories of barriers to the implementation of electronic medical records which consist of technical concerns, initial and maintenance costs, security concerns, lack of technical support, user resistance, system interoperability capability, lack of infrastructures, and productivity concerns.